Revitalization Ideology and Pillars of Nationality in Citizens Dynamics Pre-Post Legislative and Executive Elections on 2024 - Abdillah, Muhammad Helmy; Fuady, Najmi; Makie, Haji Ahmad (Jurnal Kewarganegaraan, 2025)
The Community members have become vulnerable to division, particularly due to the polarization of their election choices. Whether economic, social, or political, campaign promises fuel this polarization. Revitalized Pancasila and the pillars of nationality can to restore the dignity of the Negara Kesatuan Republik Indonesia and prevent its fragmentation. The dissemination of Pancasila ideological values and the pillars of nationality is an agenda that can provide an explicit understanding of the homogenization of national and state life ethics. This activity aims to assess the influence of the socialization of the Pancasila ideology and the values of the pillars of nationality on social dynamics after the 2024 election. The results indicate that while respondent recognizes these values as noble and should implement them, they solely base their implementation on religious mu’amalah. This means that if a member of society has low religious knowledge, the potential for violating the ethics and ideological values of Pancasila and its national pillars is also quite high. Therefore, to lessen the threat of post-election division, an understanding of national insight, which encompasses the values of the Pancasila as ideology and the pillars of nationality, must accompany an understanding of religion.